2021
DOI: 10.7150/ijbs.51123
|View full text |Cite
|
Sign up to set email alerts
|

miR-340: A multifunctional role in human malignant diseases

Abstract: MicroRNAs (miRNAs) are a class of short non-coding RNAs of approximately 22 nucleotides in length, which function by binding to the 3' UTR sequences of their target mRNAs. It has been reported that dysregulated miRNAs play pivotal roles in numerous diseases, including cancers, such as gastric, breast, colorectal, ovarian, and other cancers. Recent research efforts have been devoted to translating these basic discoveries into clinical applications that could improve the therapeutic outcome in patients with canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 116 publications
2
23
0
Order By: Relevance
“…miR-340-5p, which localized in 5q35, has been identified to contribute to participate in the initiation and progression of several diseases. Recently, miR-340-5p has been revealed that participates in the initiation and progression of tumor by targeting multiple oncogenes, such as c-Met, FHL2, ROCK1, and SKP2 [ 11 ]. Importantly, numerous evidences showed that induced miR-340-5p expression promotes cellular apoptosis and suppresses cell viability, thus inhibiting tumor development [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-340-5p, which localized in 5q35, has been identified to contribute to participate in the initiation and progression of several diseases. Recently, miR-340-5p has been revealed that participates in the initiation and progression of tumor by targeting multiple oncogenes, such as c-Met, FHL2, ROCK1, and SKP2 [ 11 ]. Importantly, numerous evidences showed that induced miR-340-5p expression promotes cellular apoptosis and suppresses cell viability, thus inhibiting tumor development [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, miR-20a overexpression was positively linked to the stemness characteristics and poor prognosis of BC, which might be the pro-oncogene associated with stemness progression of breast cancer. In fact, miR-340 has been widely reported as a tumor suppressor ( 49 ). In BC, miR-340 overexpression was shown to significantly inhibit BC cell migration and invasion ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first miRNA-targeted drug was miravirsen (SPC3649), a locked nucleic acid (LNA)-modified antisense oligonucleotide targeting miR-122, that is currently in phase II clinical trial for the treatment of hepatitis C virus infection [ 190 , 191 ]. MRX34 (miRNA Therapeutics), containing a double-stranded miR-34a mimic encapsulated in ionizable liposomes, was the first miRNA mimic to enter a phase I clinical trial in 2013 (NCT01829971) in several solid tumors and hematological malignancies [ 3 , 192 ]; however, the trial was closed due to severe immune-related adverse events [ 6 ].…”
Section: Clinical Applications Of Mirnas Focusing On Hematological Ma...mentioning
confidence: 99%
“…The biogenesis of miRNAs is a multistep process, including the transcription of primary double-stranded transcripts, nuclear processing by the RNase III endonuclease enzyme Drosha, nucleocytoplasmic export by Exportin-5, cytoplasmic cleavage by Dicer, and formation of the RNA-induced silencing complex (RISC) with Argonaute (Ago) proteins [ 4 ]. miRNAs are posttranscriptional regulators of gene expression, that function primarily by binding to the 3′ untranslated regions (3′UTR) of their target messenger RNAs (mRNAs), resulting in the inhibition of translation [ 5 , 6 ]. Depending on the microenvironment, miRNAs can target multiple mRNAs, and a single mRNA can also be targeted by several different miRNAs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation